AKTIVITAS ANTIFUNGI EKSTRAK METANOL DAUN AKASIA (Acacia mangium Willd.) TERHADAP Phytophthora sp. (Im5) SECARA IN VITRO - Wulandari, Yanti; Rahmawati, Rahmawati; Mukarlina, Mukarlina (Universitas Tanjungpura, 2020)
Phytophthora sp. are pathogenic fungi that can cause plant diseases with symptomatic rotten or known as stem base rotten disease (BPB). Acacia leaf (Acacia mangium Willd.) has secondary metabolite content so that it can be used as a source of natural antifungal substitutes for synthetic antifungal This study uses a completely randomized design (CRD) with 4 treatment levels consisting of control, extract concentration of 2 %, 3 %, and 4 %. Antifungal activity test uses food poisoning method by adding acacia leaf extract to PDA media. The results showed that the extract of acacia leaves (Acacia mangium Willd.) had an effect on inhibiting the growth of isolate Phytophthora sp. (Im5) with the decrease of fungi colony diameter. Concentration of 4 % extract is the best concentration with the very strong level of antifungal activity in inhibiting the growth of Phytophthora sp. (Im5).